2023
DOI: 10.9745/ghsp-d-22-00538
|View full text |Cite
|
Sign up to set email alerts
|

The Cost of Providing Comprehensive HIV Services to Key Populations: An Analysis of the LINKAGES Program in Kenya and Malawi

Abstract: A cost analysis of comprehensive HIV services for key populations at higher risk of infection in Kenya and Malawi showed that costs can be substantial at all program implementation levels, not just service delivery; all these costs should be considered during program planning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…This study on management characteristics was part of a broader scope of work, which began with a costing study of the LINKAGES program conducted in Kenya and Malawi for US Government FY 2018 and 2019 (1 October to 30 September). The collection of data on management practices was motivated by the results of the costing study, which suggested that differences in management practices across DICs might explain some unexplained variation in program costs [ 38 , 39 ]. The management survey was applied from 1 November 2021 to 31 January 2022 using the Survey Monkey platform.…”
Section: Methodsmentioning
confidence: 99%
“…This study on management characteristics was part of a broader scope of work, which began with a costing study of the LINKAGES program conducted in Kenya and Malawi for US Government FY 2018 and 2019 (1 October to 30 September). The collection of data on management practices was motivated by the results of the costing study, which suggested that differences in management practices across DICs might explain some unexplained variation in program costs [ 38 , 39 ]. The management survey was applied from 1 November 2021 to 31 January 2022 using the Survey Monkey platform.…”
Section: Methodsmentioning
confidence: 99%